Aux sources de l’intégration européenne : l’Alsacien Curtius et la Luxembourgeoise Aline Mayrisch - Tsuda, Masayuki (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
Alsace and Luxemburg have a lot in common. For instance, the Alsatian languageand the Luxembourgian language are close to the German language, the inhabitants of these tworegions, however, speak the French language fluently. Therefore, it is understandable that thesetwo regions were sympathetic to one another. Ernst Robert Curtius, an Alsatian, was differentfrom other German scholars in that he fostered friendship with the French writers around the“Nouvelle Revue Française”. It was Aline Mayrisch, who introduced Curtius to these writers, andher castle of Colpach in Luxemburg was meeting-place for European intellectuals. Without her,Curtius couldn’t have entertained the idea of Europe. In conclusion Curtius and Aline Mayrischcan be considered the models of EU citizens.